OCCURRENCE OF MACKEREL, RASTRELLIGER KANAGURTA (CUVIER) IN DISTANT WATERS OFF BOMBAY - Pillai, S Krishna (Indian Journal of Fisheries, 2011)
Occurrence of the Indian Mackerel Rastrelliger kanagurta in distant watersoff Bombay is reported.